Enfortumab vedotin–related cutaneous toxicity correlates with overall survival in patients with urothelial cancer: a retrospective experience - Vlachou, Evangelia; Johnson, Burles Avner; McConkey, David; Jing, Yuezhou; Matoso, Andres; Hahn, Noah M.; Hoffman-Censits, Jean (Frontiers in Oncology, 2024)
Enfortumab vedotin (EV) is an antibody drug conjugate approved for advanced urothelial cancer, consisting of a monomethyl auristatin E (MMAE) payload linked to a human monoclonal antibody targeting nectin-4. No validated biomarker predictive of or correlated with response exists for EV. Cutaneous toxicity is among the most common EV-related toxicities, and typically emerges in early cycles. This retrospective experience of patients with urothelial cancer treated with EV monotherapy evaluated whether EV-related cutaneous toxicity correlated with improved outcomes including progression free (PFS) and overall (OS) survival and overall response rate (ORR). Patients treated with EV monotherapy at Johns Hopkins were identified and baseline characteristics, treatment and toxicity details were extracted through chart review. Univariable Cox hazard ratios (HR) were calculated for assessing the effect of baseline patient characteristics and cutaneous toxicity in PFS and OS. Based on the univariable analysis and known risk factors all subsequent analyses were adjusted for: Eastern Cooperative Oncology Group performance status, visceral metastases at baseline, gender as well as EV dose, and weight to account for dosing differences. Multivariable Cox proportional HR were used for comparing PFS and OS between patients with and without cutaneous toxicity, assessing toxicity and EV dose as a time-dependent variables. Adjusted p-values were calculated to compare Overall Response Rate (ORR) and Disease Control Rate (DCR) between groups using the Poisson regression model.Of the 78 patients analyzed, 42 (53.8%) experienced EV-related cutaneous toxicity which appeared early during treatment (median time to occurrence 0.5 months from EV initiation). Cutaneous toxicity correlated with significantly improved OS (HR: 0.48 95%CI: 0.25, 0.9; P=0.0235), ORR (68.3% vs 20.7%, P=0.0033) and DCR (82.9% vs 48.3%, P=0.0122). Median PFS was numerically longer in the cutaneous toxicity group (6.3 vs 1.7 months), though no significance was achieved in the multivariable analysis (HR: 0.62 95%CI: 0.35, 0.108; P=0.0925).In this retrospective study EV-related cutaneous toxicity was associated with improved patient outcomes. Confirming this observation and understanding its mechanism could lead to discovery of a new clinical biomarker of EV response that can emerge in the first cycle.